2021
DOI: 10.1007/s12079-021-00640-4
|View full text |Cite
|
Sign up to set email alerts
|

The network map of Elabela signaling pathway in physiological and pathological conditions

Abstract: Elabela (ELA; also called Apela and Toddler) is one of the recently discovered ligand among the two endogenous peptide ligands (Apelin and Elabela) of the apelin receptor (APLNR, also known as APJ). Elabela-induced signaling plays a crucial role in diverse biological processes, including formation of the embryonic cardiovascular system and early placental development by reducing the chances of occurrence of preeclampsia during pregnancy. It also plays the major role in the renoprotection by reducing kidney inj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…APJ has been reported as a predominant receptor of ELA and Apelin (6,34). One main downstream signaling pathway of APJ consists of Akt, mTOR, and P70S6K (35), which primarily regulate cell proliferation, apoptosis, and migration. As expected, compared with sham control, APJ expression was significantly increased in the MI group (2.56-fold), and it was more increased in the MIA group (P < 0.01, compared with the MI group) and further elevated in the MIAE group (P < 0.01, compared with the MIA group; Fig.…”
Section: Resultsmentioning
confidence: 99%
“…APJ has been reported as a predominant receptor of ELA and Apelin (6,34). One main downstream signaling pathway of APJ consists of Akt, mTOR, and P70S6K (35), which primarily regulate cell proliferation, apoptosis, and migration. As expected, compared with sham control, APJ expression was significantly increased in the MI group (2.56-fold), and it was more increased in the MIA group (P < 0.01, compared with the MI group) and further elevated in the MIAE group (P < 0.01, compared with the MIA group; Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Our results found that ELA-32 could treat TGF-β1-induced EMT of HPMCs from the aspects of morphology and protein expression. The ELA-mediated activation of the PI3K/AKT pathway produces protective effects in kidney disease ( Dagamajalu et al, 2022 ). However, the activation of this pathway promotes the occurrence of PF in the peritoneal tissues of patients on PD.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, a second endogenous ligand for APJ was discovered and named Toddler/ELABELA. Mature ELABELA is a 32 amino acid peptide found in the prostate, kidney, heart and blood vessels 8 . Apelin-13 and ELABELA-32 can be spontaneously modified by cyclization of the glutamine in N-terminus to produce pyroglutamylated apelin-13 (Pyr-apelin-13) or ELABELA-32 (Pyr-ELABELA-32), potentially increasing their plasma stability [8][9][10] .…”
Section: Introductionmentioning
confidence: 99%
“…Mature ELABELA is a 32 amino acid peptide found in the prostate, kidney, heart and blood vessels 8 . Apelin-13 and ELABELA-32 can be spontaneously modified by cyclization of the glutamine in N-terminus to produce pyroglutamylated apelin-13 (Pyr-apelin-13) or ELABELA-32 (Pyr-ELABELA-32), potentially increasing their plasma stability [8][9][10] . In recent years, the apelinergic system has emerged as a potential candidate for its beneficial role in angiogenesis, and on cardiovascular and metabolic functions.…”
Section: Introductionmentioning
confidence: 99%